The Relationship Between Knowledge and Assessment of Pregnant Women with the Utilization of Dental Health Services - Aprilia Martha Bakoil; Dinah Charlota Lerik; Sabina Gero (Health Notions, 2020)
Improving the optimal health status requires commitment and continuous effort so that a sub-standard development goals (SDGS) program is formed, one of which aims to tackle health problems in pregnant women. Dental and oral disease during pregnancy is a public health problem. The incidence of dental and oral diseases during this period is due to a lack of knowledge about oral health maintenance. The low use of service facilities by the community is related to treatment seeking behavior and ill-health concepts from the community. The purpose of the study was to analyze the relationship of knowledge and assessment of pregnant women with the use of dental health services at the Dental Clinic at the Health Centers in Kupang City. The design of this research was cross-sectional. The samples were 250 respondents, selected using proportional random sampling technique. Data were collected using a questionnaire as an instrument, then analyzed using ordinal regression test. Based on the data analysis results, it could be concluded that there was relationship between knowledge and assessment of pregnant women with the utilization of dental and oral health services in Public Health Center in Kupang City. Keywords: knowledge; pregnant women; utilization; dental and oral health services